Towards More Inclusive Elections: State of the Art and Challenges of Electronic Voting for People with Disabilities in Developing Countries. - Noriega Zapata, Jomark Pablo; Vargas, Ana; Castañeda, Jorge; Bernuy, Augusto (Disability, CBR & Inclusive Development)
Aim: This study examines the current state of electronic voting (e-voting) technologies and their implications for accessibility for people with disabilities, with particular attention to developing countries. It aims to identify key technological approaches, structural barriers, and design gaps affecting inclusive electoral participation. Method: A systematic review was conducted using the PRISMA methodology, analyzing publications from 2018 to 2023 in databases such as Scopus, Web of Science, Science Direct, Wiley, and IEEE. The review focused on studies addressing e-voting technologies explicitly linked to accessibility and disability inclusion, excluding works that discussed electronic voting without reference to people with disabilities. Results: The findings highlight blockchain technology as a promising solution due to its security and transparency features. However, major barriers remain, including the digital divide, lack of inclusive design, and absence of legal frameworks supporting electronic voting for people with disabilities. While some countries, such as Estonia, have successfully implemented remote voting, there are still no widespread solutions tailored to people with disabilities in developing regions. Conclusions: The findings highlight the need for e-voting systems that integrate accessibility requirements from the design stage, ensuring usability, autonomy, and non-stigmatizing participation. Future research should advance toward pilot implementations of accessible e-voting systems in developing countries, combining biometric authentication and assistive technologies within inclusive public policy frameworks.